2022
DOI: 10.3389/fnmol.2022.1028223
|View full text |Cite
|
Sign up to set email alerts
|

Function of brain-derived neurotrophic factor in the hypothalamus: Implications for depression pathology

Abstract: Depression is a prevalent mental health disorder and is the number one cause of disability worldwide. Risk factors for depression include genetic predisposition and stressful life events, and depression is twice as prevalent in women compared to men. Both clinical and preclinical research have implicated a critical role for brain-derived neurotrophic factor (BDNF) signaling in depression pathology as well as therapeutics. A preponderance of this research has focused on the role of BDNF and its primary receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 138 publications
0
3
0
1
Order By: Relevance
“…These brain areas are known to be involved in reward-related reinforcement learning that leads to behavioral changes [ 114 ] . High levels of BDNF and its main receptor TrkB have been found across hypothalamic nuclei, including the SCN [ 115 116 ] . BDNF has been suggested to mediate beneficial effects of exercise and intermittent fasting on cognitive functions [ 53 ] .…”
Section: Bdnf Controls the Access For Photic Input In The Scnmentioning
confidence: 99%
“…These brain areas are known to be involved in reward-related reinforcement learning that leads to behavioral changes [ 114 ] . High levels of BDNF and its main receptor TrkB have been found across hypothalamic nuclei, including the SCN [ 115 116 ] . BDNF has been suggested to mediate beneficial effects of exercise and intermittent fasting on cognitive functions [ 53 ] .…”
Section: Bdnf Controls the Access For Photic Input In The Scnmentioning
confidence: 99%
“…Badirudi burmuinetik eratorritako faktore neurotrofikoa (BDNF; Brain-Derived Neurotrophic Factor) estresaren substratu molekularra izan daitekeela, estresa pairatzen duten pertsonetan bere adierazpena murriztua dagoela aurkitu delako [53,54]. Halaber, BDNF depresioaren arrisku-faktore garrantzitsua kontsideratzen da eta bere mailak gutxituak aurkitu dira egoera hau pairatzen duten gizakietan [55][56][57].…”
Section: Estresa Depresio Nagusia Eta Sistema Neurotrofikoaunclassified
“…Furthermore, it has been demonstrated that apoptotic elements, which are considered responsible for manifestations linked to the pathophysiology of AD, interact with various signaling molecules, including BDNF/TrkB, and downstream signaling pathways [6]. Also, clinical and preclinical research demonstrates that the alteration of BDNF/TrkB-mediated signaling is involved in the pathology of depression [7].…”
Section: Introductionmentioning
confidence: 99%